2021
DOI: 10.1177/1550147721996248
|View full text |Cite
|
Sign up to set email alerts
|

Game algorithm based on link quality: Wireless sensor network routing game algorithm based on link quality

Abstract: Aiming at the problems of low data transmission efficiency and uneven energy consumption caused by unreliable link communication in the routing process of wireless sensor networks, this article designs a routing game algorithm based on link quality. In this article, the index for evaluating link quality is defined first. Then, the link quality, node residual energy, and minimum jump transmission strategy are integrated into the utility function to establish a game model to determine the best next hop transmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The better is the utility function the better is the proposed algorithm [13]. From the available literature [14]- [20], it has been observed that most of the researchers have considered (i) bit error rate (BER) (ii) signal-to-interference-plus-noise ratio (SINR), (iii) energy consumption (iv) throughput, and (v) quality of service network metrics to formulate the utility function.…”
Section: Introductionmentioning
confidence: 99%
“…The better is the utility function the better is the proposed algorithm [13]. From the available literature [14]- [20], it has been observed that most of the researchers have considered (i) bit error rate (BER) (ii) signal-to-interference-plus-noise ratio (SINR), (iii) energy consumption (iv) throughput, and (v) quality of service network metrics to formulate the utility function.…”
Section: Introductionmentioning
confidence: 99%
“…Also, there is a lot of interference when using TDMA. d) With high mobility rate and reserved slot allocation, there is high rate of data collision and information loss.There is need for further research that will use a better scheduling framework to reduce, information loss as a result of interference of the radio frequency (RF), reduce delay due to the multi hop nature of the network and reduce energy consumption across the network Zhanjun, Jiaojiao, Jianwu, Xiaochao & Nanjiang (2021),. "Game algorithm based on link quality: Wireless sensor network routing game algorithm based on link quality", developed a game-founded routing algorithm centred on the quality of the link.…”
mentioning
confidence: 99%